ATP Binding by Monarch-1/NLRP12 Is Critical for Its Inhibitory Function - Ye, Zhengmao (American Society for Microbiology (ASM), 2008)
The recently discovered nucleotide binding domain-leucine rich repeat (NLR) gene family is conserved from plants to mammals, and several members are associated with human autoinflammatory or immunodeficiency disorders. This family is defined by a central nucleotide binding domain that contains the highly conserved Walker A and Walker B motifs. Although the nucleotide binding domain is a defining feature of this family, it has not been extensively studied in its purified form. In this report, we show that purified Monarch-1/NLRP12, an NLR protein that negatively regulates NF-κB signaling, specifically binds ATP and exhibits ATP hydrolysis activity. Intact Walker A/B motifs are required for this activity. These motifs are also required for Monarch-1 to undergo self-oligomerization, Toll-like receptor- or CD40L-activated association with NF-κB-inducing kinase (NIK) and interleukin-1 receptor-associated kinase 1 (IRAK-1), degradation of NIK, and inhibition of IRAK-1 phosphorylation. The stable expression of a Walker A/B mutant in THP-1 monocytes results in increased production of proinflammatory cytokines and chemokines to an extent comparable to that in cells in which Monarch-1 is silenced via short hairpin RNA. The results of this study are consistent with a model wherein ATP binding regulates the anti-inflammatory activity of Monarch-1.